Use the seeds of chia seeds as ingredient of milled half-finished foodstuffs - Golembovska, N. V.; Slobodyanyuk, N. M. (НУБіП України, 2018)
There are given results of sensory analysis of flavor and some other properties of milled masses of freshwater fish enriched by the non-traditional raw material (seed of chia seeds). The conclusion on positive effect on properties of proposed compositions over those ones of the standard sample of force-fish was made on comparing of base profiles of their basic properties. The cutlets made of mass modified by vegetative ingredient had the plastic and dense consistency on their cut. The positive results of their organoleptic analysis evidenced expediency of adding of proposed vegetative ingredient to milled mass of fish. The criteria proved such conclusion were general expression of taste, aroma and harmonicity of flavor of cutlets made of mixes of developed composition.
Використання насіння чіа в якості інгредієнта подрібнювання напівфабрикатів продуктів харчування
Наводяться результати сенсорного аналізу смаку і деякі інші властивості подрібненої маси прісноводних риб збагаченого нетрадиційної сировини (насіння Насіння чіа). Висновок на позитивний вплив на властивості запропонованої композиції за ті стандартного зразка форс-риба був зроблений на порівнянні базових профілів їх основні властивості.
Keywords: Fish cutlets; vegetative raw materials; chia seeds; organoleptic testing; flavor; taste; profilogram; рибні котлети; насіння чіа; аромат; смак; профілограм